Complete and complete integral convergence for arrays of row wise widely negative dependent random variables under the sub-linear expectations. Issue 9 (25th March 2022) - Lu, Dawei; Meng, Yao
Abstract: In this article, complete and complete integral convergence theorems are obtained for arrays of row wise widely negative dependent random variables under the sub-linear expectations. We improve the results by (Lin and Feng 2019 ) and extend some complete moment convergence theorems in (Wu, Wang, and Rosalsky 2018 ) from the classical probability space to the sub-linear expectation space.